Peningkatan Kualitas 4G untuk Mendorong Minat Belajar dan Pengembangan Ekonomi Masyarakat Selama Pandemi Covid-19 di Dusun Tinggarjaya, Sukaharja, Kabupaten Bogor - Andi Arfian; Syafrianto Syafrianto; Ani Yoerani; Juarmi Siregar; Suhardoyo Suhardoyo (Universitas Mathla'ul Anwar Banten, 2021)
4G QUALITY IMPROVEMENT TO ENCOURAGE LEARNING INTEREST AND COMMUNITY ECONOMIC DEVELOPMENT DURING THE COVID-19 PANDEMIC IN TINGGARJAYA HAMLET, SUKAHARJA, BOGOR REGENCY. The use of information teknology in the economy and as a means of education for rural communities is very inportant and beneficial in both improving the performance of village information systems. With a good internet network, The delivery of information from villages to cities can run more quickly. The use of the internet for villages is still lacking due to the lack of communication tools and knowledge of villagers in the use of the internet and the basic Difference in signal betwen villages and cities is that 4G internet access is still unstable due to the hilly topology of the area and uneven distribution of the population from the problems above, We carry out community service by making internet access accessible, especially in the mass covid-19 .internet that is needed by resident especially student from the result of this service we hope that the internet acces that we bukid can be useful for interest in learning and increase the economic potential of the village.